PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DITINJAU DARI GREEN ACCOUNTING DAN KARAKTERISTIK PERUSAHAAN - Fadlilah, Kharisma; Mutmainah, Ina (Perwira Journal of Economics & Business, 2024)
Corporate Social Responsibility has an important role because it meets regulations, laws & regulations; as a corporate social investment to get a positive image; part of the company's business strategy; part of the company's risk management to reduce and avoid social conflicts. Corporate Social Responsibility in this case shows its concern for the sustainability of development but remains balanced in the economy and environment. This will give the public confidence in the company. This research includes a type of causality research with quantitative methods. The population of this study is companies listed in the Jakarta Islamic Index for the 2017-2022 period. The sample in the study was the annual report of companies listed in the Jakarta Islamic Index for the 2017-2022 period. The results of this study show that green accounting, liquidity, profitability and company size do not affect corporate social responsibility, while leverage has a positive effect on corporate social responsibility. Simultaneously, the variables of green accounting, leverage, liquidity, profitability and company size affect corporate social responsibility